2019
DOI: 10.1111/evo.13881
|View full text |Cite
|
Sign up to set email alerts
|

Subtle, pervasive genetic correlation between the sexes in the evolution of dimorphic hummingbird tail ornaments*

Abstract: Male hummingbirds have repeatedly evolved sexually dimorphic tails that they use as ornaments during courtship. We examine how male ornament evolution is reflected in female morphology. Lande's two‐step model of the evolution of dimorphism predicts that γ (the genetic correlation between the sexes) causes trait elaboration to first evolve quickly in both sexes, then dimorphism evolves more slowly. On the hummingbird phylogeny, tail length does not fit this two‐step model; although hummingbirds repeatedly evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…This challenges the phylogenetic studies which showed higher frequency in gain and loss of ornaments in females compared to males (Wiens 2001) and which have been taken as evidence that female ornaments are genetically unconstrained. Though other studies have proposed genetic constraints or adaptive advantages as explanations for female ornamentation, Clark and Rankin (2020) show that genetic correlation could finely shape female ornament morphology across a bird family.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…This challenges the phylogenetic studies which showed higher frequency in gain and loss of ornaments in females compared to males (Wiens 2001) and which have been taken as evidence that female ornaments are genetically unconstrained. Though other studies have proposed genetic constraints or adaptive advantages as explanations for female ornamentation, Clark and Rankin (2020) show that genetic correlation could finely shape female ornament morphology across a bird family.…”
mentioning
confidence: 71%
“…Clark and Rankin () do not find evidence for the sequence of events predicted by Lande in the phylogeny (Fig. ).…”
mentioning
confidence: 89%
See 3 more Smart Citations